Distribution of Ophioglossum reticulatum L. in South America : A case of long-distance jump dispersal? - Meza Torres, Esteban I. (2014)
Fil: Meza Torres, Esteban I.. Instituto de Botánica del Nordeste. CONICET-UNNE. Corrientes; Argentina